Advanced Entrepreneurship - Rwigema, Henry (Oxford University Press, 2004)
Advanced Entrepreneurship represents the only South African book on small business management or entrepreneurship at this level available to students. The text covers standard entrepreneurial theory from a southern African perspective. In addition it includes a discussion of contemporary issues facing entrepreneurs, such as strategic management and technology as tools of the businessperson. The text provides advice on the legal framework in which an entrepreneur must function, and sources of finance for the venture. It also examines issues around e-commerce and globalization. There is a discussion of the specific dilemmas - such as the focus on empowerment - facing the South African entrepreneur. The book includes a number of fully researched case examples featuring successful South African businesspeople. Examples from neighbouring states broaden the relevance of the discussion